Acidification by atmospheric deposition: evaluation report. Verzuring door atmosferische depositie: evaluatierapport - "Manuel, A R"; "van Aalst, R M"; "Bastiaens, H"; "Bresser, A H.M."; "Don, A"; "Zoetelief, J" (Ministerie van Landbouw en Visserij,Hague, Netherlands, 1984)
Due to anthropogenic activities atmospheric precipitation of the most important acidifying substances, sulfur dioxide, nitrogen oxides, and ammonium compounds in the Netherlands has increased the natural level at least 5 times. Yearly damage is estimated at tens to hundred millions of guilders. Damage to forests amounts to billions of guilders. There are numerous changes in natural ecosystems like the decrease of species numbers, vanishing of plants and animals from food chains, decreasing fertility of plants and animals. Besides there is a general lessening of vitality and longevity, especially of forests. With respect to emission of acidifying substances, human activities are clearly not adjusted to natural ecologies. Some surface waters and soils are irreversibly changed. At long term others can be brought to their original quality. Recovery of forests is possible by decreasing acid precipitations to about 20% of the present level.
Keywords: "54 ENVIRONMENTAL SCIENCES"; "ACID RAIN"; "ENVIRONMENTAL EFFECTS"; "AQUATIC ECOSYSTEMS"; "ACIDIFICATION"; "TERRESTRIAL ECOSYSTEMS"; "ATMOSPHERES"; "GROUND WATER"; "NITROGEN OXIDES"; "PLANTS"; "SOILS"; "SULFUR DIOXIDE"; "SURFACE WATERS"; "ATMOSPHERIC PRECIPITATIONS"; "CHALCOGENIDES"; "ECOSYSTEMS"; "HYDROGEN COMPOUNDS"; "NITROGEN COMPOUNDS"; "OXIDES"; "OXYGEN COMPOUNDS"; "RAIN"; "SULFUR COMPOUNDS"; "SULFUR OXIDES"; "WATER"; "510200* - Environment, Terrestrial- Chemicals Monitoring & Transport- (-1989)"